Ground-Based Interferometric Radar Systems for Natural Hazard Real-Time Emergency Monitoring - Pettinari, Alessandro; Twardzik, Matthias; Telleschi, Giulio (International Conference on Information and Communication Technologies for Disaster Management (Online), 2023)
Climate change, combined with effects of man-made activities, are progressively increasing the level of risk of natural hazard with subsequent pressure on population and Critical Infrastructures, requiring the adoption of accurate and effective monitoring technologies to provide real-time alerting, either in case of potential failures or after a natural disaster. Usually, monitoring activities are still based on the deployment of multiple contact sensors, which require access to the target with important implications on safety especially whenever the affected area is deemed to be unstable and subject to potential failures. Ground-Based Interferometric Radars (GB-InRa), widely adopted by the Mining Industry in the last fifteen years, provide remote sensing capability allowing to autonomously monitor wide areas or entire structures with sub-millimetric accuracy and without the need for contact sensors or personnel to manage the system; thanks to its intrinsic characteristics, Radar Interferometry can be a fundamental asset to guarantee a 24/7, real-time flow of information on failure precursors and timely alerts as soon as there are exceedances of the user-defined alarm thresholds.